Bacterial Chromosome Replication and DNA Repair During the Stringent Response - Sinha, Anurag Kumar; Løbner-Olesen, Anders; Riber, Leise (Frontiers in Microbiology, 2020)
The stringent response regulates bacterial growth rate and is important for cell survival under changing environmental conditions. The effect of the stringent response is pleiotropic, affecting almost all biological processes in the cell including transcriptional downregulation of genes involved in stable RNA synthesis, DNA replication, and metabolic pathways, as well as the upregulation of stress-related genes. In this Review, we discuss how the stringent response affects chromosome replication and DNA repair activities in bacteria. Importantly, we address how accumulation of (p)ppGpp during the stringent response shuts down chromosome replication using highly different strategies in the evolutionary distant Gram-negative Escherichia coli and Gram-positive Bacillus subtilis. Interestingly, (p)ppGpp-mediated replication inhibition occurs downstream of the origin in B. subtilis, whereas replication inhibition in E. coli takes place at the initiation level, suggesting that stringent cell cycle arrest acts at different phases of the replication cycle between E. coli and B. subtilis. Furthermore, we address the role of (p)ppGpp in facilitating DNA repair activities and cell survival during exposure to UV and other DNA damaging agents. In particular, (p)ppGpp seems to stimulate the efficiency of nucleotide excision repair (NER)-dependent repair of DNA lesions. Finally, we discuss whether (p)ppGpp-mediated cell survival during DNA damage is related to the ability of (p)ppGpp accumulation to inhibit chromosome replication.